Activation of AMPK by Buddleja officinalis Maxim. Flower Extract Contributes to Protecting Hepatocytes from Oxidative Stress. (3rd April 2017) - Jung, Ji Yun; Lee, Chul Won; Park, Sang Mi; Jegal, Kyung Hwan; Kim, Jae Kwang; Park, Chung A.; Cho, Il Je; Jung, Dae Hwa; An, Won G.; Ku, Sae Kwang; Zhao, Rongjie; Kim, Sang Chan
Abstract : The Buddleja officinalis Maxim. flower is used in traditional Chinese and Korean medicine to treat inflammation, vascular diseases, headache, and stroke, as well as enhance liver function. This research investigated the effects of B. officinalis Maxim. flower extract (BFE) on hepatotoxicity. The cytoprotective effects and mechanism of BFE against severe mitochondrial dysfunction and H2 O2 production in hepatotoxicity induced by coadministration of arachidonic acid (AA) and iron were observed in the HepG2 cell line. In addition, we performed blood biochemical, histopathological, and histomorphometric analyses of mice with carbon tetrachloride- (CCl4 -) induced acute liver damage. BFE inhibited the AA + iron-mediated hepatotoxicity of HepG2 cells. Moreover, it inhibited mitochondrial dysfunction, H2 O2 production, and glutathione depletion mediated by AA + iron in the same cells. Meanwhile, the cytoprotective effects of BFE against oxidative stress were associated with the activation of AMP-activated protein kinase (AMPK). In particular, based on the histopathological observations, BFE (30 and 100 mg/kg) showed clear hepatoprotective effects against CCl4 -induced acute hepatic damage. Furthermore, it inhibited 4-hydroxynonenal and nitrotyrosine immunoreactivity in hepatocytes. These results provide evidence that BFE has beneficial hepatoprotective effects against hepatic damage via the activation of AMPK pathway. Accordingly, BFE may have therapeutic potential for diverse liver disorders.